2005
DOI: 10.1002/lt.20466
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate in combination with calcium and vitamin D prevents bone loss after orthotopic liver transplantation: A prospective single-center study

Abstract: Bone loss is a common complication in patients before and after liver transplantation (LT). The aim of this study was to investigate the efficacy of prophylactic treatment with bisphosphonates after LT in preventing progressive bone loss in LT patients. We included 136 patients with end-stage liver diseases awaiting LT. Bone mineral density (BMD) (by dual X-ray absorptiometry) and markers of bone metabolism were determined before, and 4, 12, 24, 36, and 48 months after LT. All patients received vitamin D and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 56 publications
(71 reference statements)
8
34
0
3
Order By: Relevance
“…6 Nonrandomized trials have shown that treatment with biphosphate drugs, which inhibit osteoclastic-medi-ated bone resorption, appears to be effective in preventing bone loss. 7 This randomized, double-blind, controlled trial by Crawford et al, using biphosphate treatment with zoledronic acid, confirmed the conclusions of prior studies and showed that zoledronic acid prevents bone loss during the first yr following transplantation. Study patients were given 5 infusions of zoledronic acid (4 mg in 100 mL of normal saline, administered over 15 minutes).…”
Section: Commentssupporting
confidence: 75%
See 2 more Smart Citations
“…6 Nonrandomized trials have shown that treatment with biphosphate drugs, which inhibit osteoclastic-medi-ated bone resorption, appears to be effective in preventing bone loss. 7 This randomized, double-blind, controlled trial by Crawford et al, using biphosphate treatment with zoledronic acid, confirmed the conclusions of prior studies and showed that zoledronic acid prevents bone loss during the first yr following transplantation. Study patients were given 5 infusions of zoledronic acid (4 mg in 100 mL of normal saline, administered over 15 minutes).…”
Section: Commentssupporting
confidence: 75%
“…This topic has been highlighted in Liver Transplantation. [2][3][4][5][6][7] Osteoporosis is a serious complication of liver transplantation, resulting in posttransplantation fractures at a rate of 6 to 17% and even higher. 4,5,7 In recent years, the incidence has decreased, with the lower rate being attributed to the smaller dose of glucocorticoids now administered following transplantation.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shane et al showed minimal bone loss after heart transplantation treated with either calcitriol or alendronate without a detectable advantage for either substance (28). Another investigator of an uncontrolled trial suggested that alendronate was efficacious in preventing bone loss associated with LT (13). No significant differences could be shown in their trial and Crawford et al pointed out in a randomized controlled setting, that zoledronic acid can prevent bone loss within the first year after liver transplantation, but his trial was not powered to assess fractures (29).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of pamidronate on indirect parameters, such as bone mineral density (BMD), have been shown in patients undergoing heart, liver, lung and kidney transplantation (8)(9)(10)(11)(12). One investigator suggested that aledronate is efficacious in preventing the natural course of bone loss associated with LT (13). However, measurements of BMD at the lumbar spine do not accurately predict the risk of fractures after LT (14).…”
Section: Introductionmentioning
confidence: 99%